Prospective randomized comparison between axial- and lateral-viewing capsule endoscopy systems in patients with obscure digestive bleeding - Pioche, Mathieu; Vanbiervliet, Geoffroy; Jacob, Philippe; Duburque, Clothilde; Gincul, Rodica; Filoche, Bernard; Daudet, Jacques; Filippi, Jérôme; Saurin, Jean-Christophe (Endoscopy, 2014)
Background and study aim: Video capsule endoscopy (VCE) is recommended as the first exploration in obscure digestive bleeding. The efficiency of the PillCam SB2 (Given Imaging) has been widely reported. The CapsoCam capsule (Capsovision) has four cameras allowing the exploration of the small bowel through 360° lateral viewing. This system does not include a recording system so the capsule has to be retrieved by the patient after expulsion in order for the film to be downloaded. The aim of this study was to evaluate diagnostic concordance (kappa value) of the PillCam SB2 and CapsoCam capsules in the same patients.Methods: This was a prospective comparative study in four French referral endoscopy units. Consecutive patients ingested the two capsules 1 hour apart and in a randomized order. Results: In the 73 included patients there were 13 technical issues (11 CapsoCam, 2 PillCam SB2). Of the 60 patients with analyzable data, and following expert review of all discordant cases, a concordant positive diagnosis was obtained in 23 (38.3 %) and a negative diagnosis was obtained and 26 patients (43.3 %). Concordance was good, with a kappa value of 0.63 in analyzable patients, and 46.7 % diagnosis with CapsoCam vs. 48.3 % with PillCam SB2. CapsoCam and PillCam SB2 procedures identified 81.8 % (27 /33) and 84.8 % (28 /33) of positive patients, respectively (P = 0.791). In a per lesion analysis, the CapsoCam capsule detected significantly more lesions (108 vs. 85 lesions; P = 0.001). Reading time was longer for CapsoCam procedures (32.0 vs. 26.2 minutes; P = 0.002).Conclusion: This study shows comparable efficiency of the CapsoCam and PillCam SB2 capsule systems in terms of diagnostic yield and image quality.